348. Etiology of Eosinophilic Meningitis in Korea - Park, Sunghee (Open Forum Infect Dis, 2020)
BACKGROUND: Eosinophilic meningitis is defined as the presence of more than 10 eosinophils per mm(3) in the cerebrospinal fluid (CSF), or eosinophils accounting for more than 10 percent of CSF leukocytes in a patient with symptoms or signs suggestive of acute meningitis. Parasites are known to be the most common cause of eosinophilic meningitis worldwide, but there is limited research on patients in South Korea. METHODS: We retrospectively reviewed patients with eosinophilic meningitis at a tertiary hospital in Seoul, South Korea, from 2004 to 2018. Patients who were suspected of having a non-infectious cause were excluded. Etiology and clinical characteristics such as age, sex, risk factors, symptoms and signs, laboratory and radiologic findings, treatment, and prognosis were identified. RESULTS: Of the 35 patients included in this study, 11 (31.4%) had parasitic causes, with 8 (22.9%) diagnosed as neurocysticercosis, and 3 (8.6%) as toxocara meningitis. Four (11.4%) were diagnosed with fungal meningitis, and underlying immunodeficiency was found in 2 of these patients. Tuberculous meningitis was suspected in 4 (11.4%), while viral and bacterial meningitis were rare causes of eosinophilic meningitis, with 2 (5.7%) and 1 (2.9%) patients, respectively. One patient with neurocysticercosis and one patient with fungal meningitis died, while 8 (22.9%) had remaining neurologic sequelae. The etiology was unknown in 13 patients (37.1%). Four of these patients received empirical anti-tuberculosis therapy, while 5 were treated empirically with acyclovir. [Image: see text] CONCLUSION: Parasite infections, especially neurocysticercosis and toxocariasis, were the most common cause of eosinophilic meningitis in South Korean patients. Fungal meningitis, while relatively rare, is often aggressive and should always be considered when searching for the cause of eosinophilic meningitis. DISCLOSURES: All Authors: No reported disclosures